Raphaël Lemkin, Genocide, Colonialism, Famine, and Ukraine - Irvin-Erickson, Douglas (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
Many words have been used to name and describe the Great Ukrainian Famine of 1932-33, including “famine” and “catastrophe,” “the Holodomor,” and now “genocide.” Was the famine genocide? Was the famine part of a genocide? Is the word genocide an exaggeration? Is naming the famine a genocide part of an attempt to dramatize events for political purposes today? Is the refusal to call the famine a genocide an act of genocide denial? This article argues that, though more than seven decades have passed and the Soviet Union has come and gone, questions about genocide in Ukraine remain intertwined in the discourses and narratives surrounding conflicts over Ukraine’s economic, political, social, and cultural position between the European Union and the Russian Federation. Given the implications of this word—“genocide”—within the context of current conflicts over Ukrainian history and identity and even sovereignty, it is important to reflect on how this concept has been used and applied. This paper analyzes conflict in Ukraine in the 1930s using Raphaël Lemkin's definition of genocide, as opposed to the legal definition established by the UN Genocide Convention, and discusses the conceptual strengths of Lemkin's definition of genocide in terms of understanding a wide-spectrum of oppressive, repressive, and violent processes of empire-building and colonization that occurred in Ukraine, and which culminated in the Holodomor.